Vertats relatives: era experiéncia dempús dera recèrca en dialectologia - Ramon Sistac (Lengas)
The research method in the dialectology and geolinguistics fields that has been experimented for more than one century now has favoured the approach of oral history as a resort to reach the informant’s readiness to speak. However this one develops a « story » motivated by likelyhood and a desire of justification for himself and in front of others rather than by veracity. The veil of silence still hiding the Spanish War generates fantasy stories on the brink of the literary genre.